Photoresist composition and metallization method
A photo resist composition with an acid labile group and inhibitors addresses hem pulling issues, enhancing the reliability of semiconductor manufacturing by preventing plating pattern collapse.
Patent Information
- Application Number
- JP2024113416
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-17
- Filing Date
- 2024-07-16
- Publication Date
- 2025-01-29
AI Technical Summary
The occurrence of hem pulling profiles in photo resist patterns during the manufacturing of semiconductor devices leads to the collapse of plating patterns, which is a critical issue in the production of smaller, more complex electronic components.
A photo resist composition comprising a polymer with an acid labile group, a first and second basic inhibitor, and a photoacid generator is used to form a plating mask, which minimizes hem pulling by controlling the dissolution profile of the resist layer.
The proposed composition effectively reduces hem pulling, preventing the collapse of plating patterns and ensuring reliable manufacturing processes for high-density electronic devices.
Smart Images

Figure 2025014122000025 
Figure 2025014122000026 
Figure 2025014122000027
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE The present disclosure relates to photoresist compositions and metallization methods. In particular, the present disclosure relates to photoresist compositions that prevent the occurrence of a tail profile in a photoresist pattern. [Background technology]
[0002] Mobile devices, devices that are part of the Internet of Things (IoT), and wearable electronics have over the years become smaller, lighter, and thinner devices that, despite their miniaturization, use larger amounts of memory and perform ever-increasing amounts of computation.
[0003] The manufacturing and packaging of these electronic devices plays an important role in size reduction. For example, flip-chip packaging methods are used to increase the density of I / O (input / output) connections between devices, especially for microprocessing units (MPUs) and dynamic random access memory (DRAM) semiconductor chips.
[0004] Metal pillar bumps, such as copper pillar bumps, are often used as flip-chip interconnects for use in electronics and optoelectronic packaging, such as flip-chip packaging of CPU and GPU integrated circuits (chips), laser diodes, and semiconductor optical amplifiers (SOAs). Metal pillar bumps provide beneficial connection resistance, high density connection, metal migration resistance, and heat dissipation properties. Metal line patterns can also be used, for example, in redistribution layers (RDLs) to provide electrical connections between two components.
[0005] Electroplating is used to manufacture metal pillar bump arrays and line patterns. After coating a photoresist layer on the copper film surface, a mask pattern is made using photolithography. Then, in the open areas of the mask pattern, metal structures are formed on the metal surface by electroplating. Then, the photoresist is removed, and the metal layer previously covered by the resist is removed by etching.
[0006] One approach to preparing plating mask patterns is the use of thick photoresist layers to meet the need for thicker and narrower pattern sizes for further increases in I / O and device density. Chemically amplified photoresists can be a suitable option to achieve faster sensitivity and improved transparency desired for higher resolution patterns. Such resist compositions include a polymer with acid labile groups, a photoacid generator (PAG) and a solvent. However, when chemically amplified resists are formed on metal layers such as copper layers, tailing profile problems have been observed due to loss of photoacid present at the interface between the metal surface and the resist. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] U.S. Patent No. 6,057,083 [Patent Document 2] U.S. Patent No. 6,136,501 [Patent Document 3] U.S. Patent No. 8,206,886 [Patent Document 4] European Patent Application Publication No. 01008913A1 [Patent Document 5] European Patent Application Publication No. 00930542A1 [Patent Document 6] US Patent Application Publication No. 2012 / 0064456A1 [Patent Document 7] U.S. Patent No. 6,042,997 [Patent Document 8] U.S. Patent No. 5,492,793 [Patent Document 9] U.S. Pat. No. 5,929,176 [Patent Document 10] U.S. Patent No. 6,090,526 [Patent Document 11] U.S. Patent No. 6,692,888 [Patent Document 12] U.S. Patent No. 6,680,159 [Patent Document 13] U.S. Pat. No. 5,843,624 [Patent Document 14] U.S. Patent No. 6,048,664 [Patent Document 15] U.S. Patent No. 6,048,662 [Patent Document 16] International Publication No. 0186353A1 Brochure [Patent Document 17] U.S. Patent No. 6,306,554 [Patent Document 18] U.S. Patent No. 7,244,542 Summary of the Invention [Problem to be solved by the invention]
[0008] The tailing of the resist pattern results in an undercut profile of the plating pattern, which can promote the collapse of the plating pattern during downstream processing. Therefore, it is desirable to eliminate the tailing of the photoresist pattern used as a plating mask. [Means for solving the problem]
[0009] As used herein, a first repeat unit of formula (3) and a second repeat unit of formula (4): [ka] (In the formula, R1 is a hydrogen atom or a substituted or unsubstituted C1-C3 alkyl, Z is a non-hydrogen substituent containing an acid labile site, and m and n are the numbers of repeating units of the first repeating unit and the second repeating unit, respectively.) and a polymer comprising the formula (6): [ka] (wherein R2 is independently C1-C3 alkyl or C1-C3 alkoxy, and p is an integer of 0 to 4). A photoresist composition is disclosed that includes the compound of the formula (I), a photoacid generator, and a solvent.
[0010] Provided herein is a photoresist composition that includes (a) a polymer, (b) one or more photoacid generators, (c) a first base quencher, (d) a second base quencher, and (e) a solvent, wherein the polymer has two repeat units: [ka] (In the formula, R1 is a hydrogen atom or a substituted or unsubstituted C1-C3 alkyl, Z is a non-hydrogen substituent providing an acid labile site, m is 20 to 90 mol % and n is 10 to 80 mol % based on all polymerization units present in the polymer.) and the photoacid generator is selected from the group consisting of N-hydroxynaphthalimide trifluoromethanesulfonate, N-hydroxynaphthalimide perfluoro-1-butanesulfonate, N-hydroxynaphthalimide camphor-10-sulfonate, N-hydroxynaphthalimide 2-trifluoromethylphenylsulfonate, N-hydroxy-5-norbornene-2,3-dicarboximide perfluoro-1-butanesulfonate, N-(trifluoromethylsulfonyloxy)phthalimide and N-hydroxy and cis-succinimide perfluorobutanesulfonate; the first basic quenching agent is selected from N-diethyldodecanamide, 2,8-dimethyl-6H,12H-5,11-methanodibenzo[b,f][1,5]diazocine (Tröger's base), 1,1-dimethylethyl 4-hydroxypiperidine-1-carboxylate, N-allylcaprolactam, ethyl-3-(morpholino)propionate, 4-(p-tolyl)morpholine, or a combination thereof; and the second basic quenching agent is selected from the group consisting of a cyclic aryl group, cyclic aryl group, and cyclic aryl group. [ka] (wherein R2 is independently C1-C3 alkyl or C1-C3 alkoxy, and p is an integer of 0 to 4). and the solids content of the photoresist composition is 10 to 60 wt %.
[0011] Provided herein is a process comprising forming a photoresist layer on a metal layer comprising (a) a polymer, (b) a photoacid generator, (c) a first base quencher, and (d) a second base quencher; patternwise exposing the photoresist layer to activating radiation; contacting the photoresist layer with an alkaline developer to remove exposed portions of the photoresist layer; immersing the metal layer in a metal plating solution and depositing metal on the metal layer in the exposed portions of the photoresist layer, wherein the polymer comprises two types of repeat units: [ka] (In the formula, R1 is a hydrogen atom or a substituted or unsubstituted C1-C3 alkyl, Z is a non-hydrogen substituent providing an acid labile site, m is 20 to 90 mol % and n is 10 to 80 mol % based on all polymerization units present in the polymer.) wherein the first basic quenching agent is selected from N-diethyldodecanamide, 2,8-dimethyl-6H,12H-5,11-methanodibenzo[b,f][1,5]diazocine (Tröger's base), 1,1-dimethylethyl 4-hydroxypiperidine-1-carboxylate, N-allylcaprolactam, ethyl-3-(morpholino)propionate, 4-(p-tolyl)morpholine, or a combination thereof, and the second basic quenching agent is represented by formula (6): [ka] (wherein R2 is independently C1-C3 alkyl or C1-C3 alkoxy, and p is an integer of 0 to 4). Also disclosed is a process, wherein the compound is [Brief description of the drawings]
[0012] [Figure 1A] 1 illustrates an exemplary embodiment of a substrate upon which a first metal layer is disposed. [Figure 1B] 1 illustrates an exemplary embodiment of depositing a photoresist layer onto a first metal layer and photopatterning the photoresist layer and the first metal layer. [Figure 1C] 1 illustrates an exemplary embodiment of developing a photoresist layer. [Figure 1D] 1 is an exemplary depiction of the deposition (by plating) of metal on a metal layer. [Figure 1E] 3 shows the plated metal structures remaining after removal of the remaining photoresist layer. [Diagram 2] Table 1 containing data from the examples is provided. [Diagram 3] Table 3 containing data from the examples is provided. [Figure 4]1 is a graph of optimal exposure energy for nominal feature size (Eop) directed to photoresist compositions versus the molar ratio of second base quencher to PAG in each composition. [Diagram 5] FIG. 1 is a plot of the weight loss of each second basic quenching agent determined using thermogravimetric analysis. [Figure 6] Table 5 is provided containing data from the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] As used herein, the terms "a," "an," and "the" do not denote limitations of quantity and should be construed to include both the singular and the plural unless otherwise indicated herein or clearly contradicted by context. "Or" means "and / or" unless otherwise stated.
[0014] As used herein, "acid labile group" refers to a group in which the bond is cleaved, optionally and typically by thermal treatment, by the catalysis of an acid, resulting in a polar group such as a carboxylic acid or alcohol group formed on the polymer, and optionally and typically the moiety connected to the cleaved bond is cleaved from the polymer. Such acids are typically photogenerated acids, in which bond cleavage occurs during post-exposure bake. Suitable acid labile groups include, for example, tertiary alkyl ester groups, secondary or tertiary aryl ester groups, secondary or tertiary ester groups with a combination of alkyl and aryl groups, tertiary alkoxy groups, acetal groups or ketal groups. Acid labile groups are also commonly referred to in the art as "acid cleavable groups", "acid cleavable protecting groups", "acid labile protecting groups", "acid leaving groups", "acid decomposable groups" and "acid sensitive groups".
[0015] Disclosed herein is a photoresist composition that reduces the tailing of a photoresist layer when used as a plating mask. The photoresist composition includes a polymer containing an acid labile group, a first base quencher, a second base quencher, and a photoacid generator. Disclosed herein is also a method for manufacturing a semiconductor that minimizes the occurrence of tailing in a photoresist layer during the manufacturing process. Footing causes undercutting of the plating pattern, which can promote the collapse of the plating pattern during further processing and reliability testing. Therefore, it is desirable to eliminate or suppress the tailing of the plating pattern.
[0016] The above-mentioned photoresist composition is disposed on a substrate to form a photoresist layer. The photoresist layer is patternwise exposed to activating radiation. The exposed photoresist layer is then developed with a basic developer, thereby removing portions of the photoresist layer to form a relief pattern. After forming the relief pattern, a metal can be plated onto the first surface of the substrate.
[0017] 1A-1E show a method of forming a plating pattern on a substrate. FIG. 1A shows a substrate 100 on which a first metal layer 102 is disposed. FIG. 1B shows coating of a photoresist layer 106 onto the metal layer 102, followed by exposure of the photoresist layer 106 to light. The photoresist layer 106 includes a photoacid generator and a polymer containing acid labile groups. After coating the photoresist layer 106, the photoresist layer 106 is patternwise exposed to activating radiation 108 through a photomask 110 having optically opaque and optically transparent regions. UV light having a wavelength between 10 nanometers and 400 nanometers can be used in photopatterning.
[0018] Figure 1C shows development of the exposed portions of the photoresist layer 106. The exposed portions of the photoresist layer 106 are removed by development, as seen in Figure 1C. After metal plating, as seen in Figure 1D, the remaining portions of the photoresist layer can be removed (stripped) from the substrate, leaving behind the plated metal structures 112. Figure 1E shows the plated metal structures 112 remaining after removal of the remaining photoresist layer.
[0019] The various layers mentioned above (shown in FIGS. 1A to 1E) and their respective compositions will now be described in detail.
[0020] substrate Examples of substrates include, but are not limited to, silicon wafers, glass substrates, and plastic substrates, optionally including one or more layers or features formed thereon. A preferred substrate is a silicon wafer.
[0021] metal layer FIG. 1A shows a substrate 100 on which a first metal layer 102 is disposed. An optional second metal layer (not shown) may be disposed on the first metal layer 102. The first metal layer may be made of, for example, titanium, silver, aluminum, gold, copper or alloys thereof. In an exemplary embodiment, the first metal layer 102 comprises titanium or copper. When a second metal layer is disposed on the first metal layer, the first metal layer preferably comprises titanium. The first metal layer may be formed using known methods, for example by chemical vapor deposition (CVD), plasma enhanced chemical vapor deposition (PECVD) or physical vapor deposition (PVD) techniques, with sputtering and plating being typical. The thickness of the first metal layer 102 is typically between 10 nm and 500 nm.
[0022] The optional second metal layer comprises tantalum, titanium, copper, silver, aluminum, gold, or alloys thereof. The second metal layer is chemically distinct from the first metal layer 102. In an exemplary embodiment, the second metal layer comprises copper. The second metal layer may be disposed on the surface of the first metal layer via chemical vapor deposition (CVD), plasma enhanced chemical vapor deposition (PECVD), physical vapor deposition (PVD), or a combination thereof. The thickness of the second metal layer is typically between 10 nm and 500 nm.
[0023] Photoresist layer 1B shows deposition of a photoresist layer 106 on the first metal layer 102. The photoresist composition 106 includes a polymer including an acid labile group, a photoacid generator, a first base quencher, and a second base quencher. The polymer includes a first repeat unit including an acid labile group. In one embodiment, the polymer includes a second repeat unit including a vinyl aromatic group.
[0024] Acid labile groups are chemical moieties that undergo a deprotection reaction in the presence of acid. Deprotection of some acid labile groups used in the examples is brought about by heat. Acetal protecting groups are easily deprotected at room temperature. The polymer of the photoresist composition undergoes a change in solubility in the developer as a result of reaction with the acid generated from the photoacid generator (contained in the photoresist composition) after soft baking, exposure to activating radiation and post-exposure baking. This is due to photoacid-induced cleavage of the acid labile group, which causes a change in the polarity of the polymer. The acid labile group can be selected from, for example, tertiary alkyl carbonates, tertiary alkyl esters, tertiary alkyl ethers, acetals and ketals. Preferably, the acid labile group is an ester group that contains a tertiary acyclic alkyl carbon or a tertiary alicyclic carbon covalently bonded to the carboxyl oxygen of the ester of the polymer. Cleavage of such acid labile groups forms a carboxylic acid group.
[0025] In one embodiment, the polymer containing acid labile groups has the following formula (1): [ka] (In the formula, Z is selected from a hydrogen atom, a substituted or unsubstituted C1-C4 alkyl, a substituted or unsubstituted C1-C4 fluoroalkyl, or a cyano group; Z 1 is a non-hydrogen substituent containing an acid labile group, the cleavage of which forms a carboxylic acid on the polymer. The polymerized units have the structure shown in
[0026] In one embodiment, the acid labile groups that upon degradation form carboxylic acid groups on the polymer preferably have the formula -C(O)OC(R 1 )3 or a tertiary ester group of the formula -C(O)OC(R 2 )2OR 3 and R 1 are each independently a linear C 1~20 Alkyl, branched C 3~20 Alkyl, monocyclic or polycyclic C 3~20 Cycloalkyl, linear C 2~20 Alkenyl, branched C 3~20 Alkenyl, monocyclic or polycyclic C 3~20 Cycloalkenyl, monocyclic or polycyclic C 6~20 Aryl or monocyclic or polycyclic C 2~20 Heteroaryl, preferably linear C 1~6 Alkyl, branched C 3~6 Alkyl or monocyclic or polycyclic C 3~10 cycloalkyl, each of which is substituted or unsubstituted; and each R 1 optionally includes as part of its structure one or more groups selected from -O-, -C(O)-, -C(O)-O-, or -S-, and any two R 1 The groups together optionally form a ring, R 2 are independently hydrogen, fluorine, linear C 1~20 Alkyl, branched C 3~20 Alkyl, monocyclic or polycyclic C 3~20 Cycloalkyl, linear C 2~20 Alkenyl, branched C 3~20 Alkenyl, monocyclic or polycyclic C 3~20 Cycloalkenyl, monocyclic or polycyclic C 6~20 Aryl or monocyclic or polycyclic C2~20 Heteroaryl, preferably hydrogen, linear C 1~6 Alkyl, branched C 3~6 Alkyl or monocyclic or polycyclic C 3~10 cycloalkyl, each of which is substituted or unsubstituted; and each R 2 optionally includes as part of its structure one or more groups selected from -O-, -C(O)-, -C(O)-O- or -S-; R 2 The groups together optionally form a ring, R 3 is a linear C 1~20 Alkyl, branched C 3~20 Alkyl, monocyclic or polycyclic C 3~20 Cycloalkyl, linear C 2~20 Alkenyl, branched C 3~20 Alkenyl, monocyclic or polycyclic C 3~20 Cycloalkenyl, monocyclic or polycyclic C 6~20 Aryl or monocyclic or polycyclic C 2~20 Heteroaryl, preferably linear C 1~6 Alkyl, branched C 3~6 Alkyl or monocyclic or polycyclic C 3~10 cycloalkyl, each of which is substituted or unsubstituted; R 3 optionally includes as part of its structure one or more groups selected from -O-, -C(O)-, -C(O)-O- or -S-, and one R 2 is R 3 together, optionally forming a ring. Such monomers are typically vinyl aromatic, (meth)acrylate or norbornyl monomers.
[0027] Suitable acid labile group-containing units include, for example, acid labile (alkyl)acrylate units such as t-butyl (meth)acrylate, 1-methylcyclopentyl (meth)acrylate, 1-ethylcyclopentyl (meth)acrylate, 1-isopropylcyclopentyl (meth)acrylate, 1-propylcyclopentyl (meth)acrylate, 1-methylcyclohexyl (meth)acrylate, 1-ethylcyclohexyl (meth)acrylate, 1-isopropylcyclohexyl (meth)acrylate, 1-propylcyclohexyl (meth)acrylate, methyladamantyl (meth)acrylate, ethyladamantyl (meth)acrylate, and the like, as well as other cyclic and acyclic (alkyl)acrylates, such as alicyclic.
[0028] Acetal and ketal acid labile groups can substitute for hydrogen atoms at the ends of alkali-soluble groups such as carboxyl groups and bond to oxygen atoms. When acid is generated, the bond between the acetal or ketal group and the oxygen atom to which the acetal-type acid dissociable dissolution inhibiting group is bonded is cleaved by the acid. Examples of such acid labile groups are described, for example, in (Patent Document 1), (Patent Document 2), (Patent Document 3), (Patent Document 4) and (Patent Document 5). Acetal and ketal groups as part of a sugar derivative structure that are cleaved to form a hydroxyl group, as described, for example, in (Patent Document 6), are also suitable.
[0029] Suitable polymers include, for example, phenolic resins containing acid labile groups. Particularly preferred resins of this class include: (i) polymers containing polymerized units of vinylphenol and acid labile (alkyl)acrylates as described above, such as those described in (US Pat. No. 5,399,613) and (US Pat. No. 5,499,623); (ii) polymers containing polymerized units of vinylphenol and optionally substituted vinylphenyl (e.g., styrene) without hydroxy or carboxy ring substituents and acid labile (alkyl)acrylates as described above, such as those described in (US Pat. No. 5,499,623); (iii) polymers containing repeat units containing acetal or ketal moieties that react with photoacid and optionally aromatic repeat units such as phenyl or phenol groups, such as those described in (US Pat. No. 5,499,623) and (US Pat. No. 5,499,623); and blends of (i), and / or (ii), and / or (iii). Such polymers are useful, for example, for imaging at wavelengths of 200 nm or more, such as 248 nm and 365 nm.
[0030] Suitable polymers include those useful for imaging at certain sub-200 nm wavelengths, such as 193 nm, such as those disclosed in U.S. Patent No. 5,399,623, and U.S. Patent No. 5,499,633 and U.S. Patent No. 5,499,623. For imaging at 193 nm wavelengths, the polymer is preferably substantially free (e.g., less than 15 mole %), and preferably completely free, of phenyl, benzyl or other aromatic groups, such groups being highly absorbing of radiation.
[0031] Other suitable polymers for use in the photoresist compositions include, for example, those that contain polymerized units of non-aromatic cyclic olefins (endocyclic double bonds), such as optionally substituted norbornenes, such as the polymers described in U.S. Patent Nos. 5,993,333 and 5,949,623. Still other suitable polymers for use in the photoresist compositions include those that contain polymerized anhydride units, particularly polymerized maleic anhydride and / or itaconic anhydride units, such as those disclosed in U.S. Patent Nos. 5,993,333 and 5,949,623.
[0032] Polymers containing repeat units containing heteroatoms, particularly oxygen and / or sulfur (but other than anhydrides, i.e., the units do not contain keto ring atoms), are also suitable for use in photoresist compositions. Heteroalicyclic units can be fused to the polymer backbone and can include fused carbon alicyclic units, such as those provided by polymerization of norbornene groups, and / or anhydride units, such as those provided by polymerization of maleic anhydride or itaconic anhydride. Such polymers are disclosed in U.S. Pat. No. 5,399,413 and U.S. Pat. No. 5,499,426. Other suitable heteroatom-containing polymers include polymers containing polymerized carbocyclic aryl units substituted with one or more heteroatom (e.g., oxygen or sulfur)-containing groups, such as hydroxynaphthyl groups, as disclosed in U.S. Pat. No. 5,499,426.
[0033] The polymer may further comprise units that contain a lactone moiety to control the dissolution rate of the polymer and the photoresist composition. Monomers suitable for use in the polymer that contain a lactone moiety include, for example: [ka]
[0034] In one embodiment, the polymer typically further comprises units that include polar groups, which enhance the etch resistance of the polymer and the photoresist composition and provide an additional means of controlling the dissolution rate of the polymer and the photoresist composition. Monomers for forming such units include, for example: [ka]
[0035] The polymer may contain one or more additional units of the types described above. Typically, the additional units of the polymer contain the same or similar polymerizable groups as those used in the monomers used to form the other units of the polymer, but may contain other different polymerizable groups in the same polymer backbone.
[0036] The polymer may also include one or more repeat units derived from the polymerization of a vinyl aromatic monomer. An exemplary vinyl aromatic monomer is styrene. In one embodiment, the polymer derived from the vinyl aromatic monomer has the following formula (2): [ka] (In the formula, a is 1 to 5; Z 2 is hydrogen or an alkyl group having 1 to 5 carbon atoms. In a preferred embodiment, a is 1 and Z 2 is hydrogen. The vinyl aromatic monomer preferably has a hydroxyl group in the para position on the aryl ring. A preferred vinyl aromatic polymer is poly(p-hydroxystyrene) (abbreviated as PHS).
[0037] In one embodiment, a polymer for use in a photoresist composition comprises a first repeat unit of formula (3) and a second repeat unit of formula (4): [ka] (wherein R1 is a hydrogen atom or a substituted or unsubstituted C1-C3 alkyl, and Z is a non-hydrogen substituent containing an acid labile site). In one embodiment, m+n (in formulas (3) and (4)) is 70 to 100 moles (mol%). In one embodiment, m is 10 to 90 mole%, preferably 25 to 80 mole%, preferably 30 to 40 mole%, and n is 10 to 90 mole%, preferably 20 to 70 mole%, based on the total polymerized units present in the polymer. In one embodiment, the molar ratio of n to m is 0.11 to 9, preferably 0.2 to 4.
[0038] When the polymer includes a third repeat unit (different from the first and second repeat units), the third repeat unit may be present in the polymer in an amount of 5 to 35 mol %, preferably 10 to 30 mol %, based on all polymerized units present in the polymer.
[0039] Exemplary polymers include, but are not limited to, for example: [ka]
[0040] Polymers suitable for use in photoresist compositions are commercially available or can be readily made by one of ordinary skill in the art. The polymer is present in a photoresist composition in an amount sufficient to render an exposed coating layer of the photoresist developable in a suitable developer.
[0041] Typically, the polymer is present in the photoresist composition in an amount of 70 to 100 weight percent based on the total solids content of the photoresist composition. w is typically less than 100,000, for example, 4000 to 100,000, more typically 4000 to 20,000 grams per mole (g / mol), as measured by gel permeation chromatography using polystyrene standards. Blends of two or more of the above polymers may be suitably used in the photoresist compositions of the invention.
[0042] The photoresist composition includes a non-ionic photoacid generator. In one embodiment, the photoresist composition may optionally include an ionic photoacid generator. It is desirable to use a photoacid generator that generates a photoacid by Norrish-I type cleavage. The Norrish-I type reaction is the photochemical cleavage or homolysis of aldehydes and ketones into two free radical intermediates. The carbonyl group accepts a photon and is excited to a photochemical singlet state. In one embodiment, the photoacid generator is represented by the formula (5): [ka] In formula (5), R4 is a hydrogen atom, a substituted or unsubstituted linear or branched C1-C 14R5 is an alkyl group, a substituted heterocyclic group, or a halogen atom, and R5 is a substituted or unsubstituted alkyl group having 1 to 18 carbon atoms, a halogen atom, or an aryl group having 6 to 20 unsubstituted carbon atoms.
[0043] Examples of suitable photoacid generators are N-hydroxynaphthalimide trifluoromethanesulfonate (NHNI-TF), N-hydroxynaphthalimide perfluoro-1-butanesulfonate (NHNI-PFBS), N-hydroxynaphthalimide camphor-10-sulfonate, N-hydroxynaphthalimide 2-trifluoromethylphenylsulfonate, N-hydroxy-5-norbornene-2,3-dicarboximide perfluoro-1-butanesulfonate, N-(trifluoromethylsulfonyloxy)phthalimide, N-hydroxysuccinimide perfluorobutanesulfonate or benzeneacetonitrile, 2-methyl-α-[2-[[(propylsulfonyl)oxy]imino]-3(2H)-thienylidene] (commercially available as IRGACURE PAG 103). In a preferred embodiment, the photoacid generator is represented by formula (5a) or (5b) as shown below: [ka] The structure may be one or more of the following:
[0044] The photoacid generator is present in the photoresist composition in an amount from 0.2 to 15 weight percent, more typically from 0.3 to 5 weight percent, and more preferably from 0.5 to 2 weight percent based on the total solids content of the photoresist composition.
[0045] As described above, the photoresist composition includes a first basic quencher and a second basic quencher. The basic quencher improves the resolution of the developed resist relief image. The first basic quencher is preferably weaker basic than common tertiary amines. The low basicity prevents the decomposition of the i-line sensitive photoacid generator during storage of the photoresist composition. The first basic quencher is selected from N-diethyldodecanamide, 2,8-dimethyl-6H,12H-5,11-methanodibenzo[b,f][1,5]diazocine (Tröger's base), 1,1-dimethylethyl 4-hydroxypiperidine-1-carboxylate, N-allylcaprolactam, ethyl-3-(morpholino)propionate, 4-(p-tolyl)morpholine, or a combination thereof.
[0046] The first basic quencher is preferably added in an amount effective to render the photoresist composition have a pKa of less than 7. The amount of the first basic quencher in the photoresist layer is preferably 0.001 to 1.0 wt %, more preferably 0.01 to 0.8 wt % or 0.02 to 0.2 wt %, based on the total weight of solids in the photoresist composition.
[0047] The second basic quenching agent comprises a 2-mercapto aromatic azole analog. In one embodiment, the aromatic azole analog comprises a thiol functional unit at the 2-position of the aromatic azole compound. If the 2-position is substituted with a chemical moiety other than thiol, such as a methyl-thio or carboxy-methylthio moiety, this does not improve the tailing profile on the copper substrate.
[0048] Examples of aromatic azole analogs include benzoxazoles. Examples of benzoxazoles that can be used as second base quenching agents include those represented by formula (6): [ka] (wherein R2 is independently C1-C3 alkyl or C1-C3 alkoxy, and p is an integer of 0 to 4). The amount of the second basic deactivator is 0.01% by weight to 1% by weight based on the total weight of the solid content in the photoresist composition. Addition of more than 1% by weight of the second basic deactivator (addition amount exceeding the chemisorption layer formation) may affect the angled pattern profile when viewed across the cross section.
[0049] The photoresist composition further comprises a solvent, which is used to solvate the polymer and promote miscibility of the various components used in the composition.
[0050] Solvents generally suitable for dissolving, dispensing and coating include anisole; alcohols such as 1-methoxy-2-propanol (also known as propylene glycol methyl ether, PGME) and 1-ethoxy-2-propanol; esters such as n-butyl acetate, 1-methoxy-2-propyl acetate (also known as propylene glycol methyl ether acetate, PGMEA), methoxyethyl propionate, ethoxyethyl propionate; ketones such as cyclohexanone, 2,6-dimethyl-4-heptanone, 2 heptanone; ethyl lactate (EL), 2-hydroxyisobutyric acid methyl ester (HBM), gamma-butyrolactone (GBL), 3-methoxypropanoic acid methyl ester, and combinations thereof.
[0051] The amount of solvent may be, for example, 25-1900% by weight, preferably 67-900% by weight, more preferably 100-150% by weight, based on the total weight of the solids of the photoresist composition. It will be understood that the "polymer" used in this context of the components in the photoresist layer may refer only to the polymer (containing acid labile groups) disclosed herein. It will be understood that the total solids includes the polymer, photodestructible base, quencher, surfactant, photoacid generator, and any additives except the solvent. The solids content of the composition may be 5-80% by weight, preferably 10-60% by weight.
[0052] The photoresist composition may include other optional ingredients such as one or more surface leveling agents (SLAs), adhesion promoters, and / or plasticizers. If used, the SLA is preferably present in an amount of 0.001 to 0.1 wt % based on the total solids content of the photoresist composition, and the adhesion promoters and / or plasticizers, if used, are each present in an amount of 0.1 to 10 wt % based on the total solids content of the photoresist composition.
[0053] A photoresist composition is applied to the first metal layer 102 to form a photoresist layer 106. In one embodiment, the photoresist layer has a thickness greater than 2 micrometers. The photoresist composition is typically applied to the surface of the metal layer by spin coating, dipping, roller coating or other conventional coating techniques. Spin coating is preferred. For spin coating, the solids content of the coating solution can be adjusted to provide the desired film thickness based on the particular coating equipment utilized, the viscosity of the solution, the speed of the coating tool, and the amount of time allowed for rotation. In one embodiment, the photoresist composition is applied in a single application.
[0054] The photoresist composition layer is then patternwise exposed to activating radiation through a photomask to create a solubility difference between exposed and unexposed regions. Referring to FIG. 1B, after deposition of the photoresist layer 106, a mask 110 is placed on the photoresist layer 106 to photopattern the photoresist layer 106. UV light having a wavelength between 10 nanometers and 500 nanometers can be used in photopatterning. The exposed portions of the photoresist layer can be removed by a suitable alkaline developer, as seen in FIG. 1C.
[0055] References herein to exposing a photoresist composition layer to radiation activating for the layer indicate that the radiation can form a latent image in the layer. The photomask has optically transparent and optically opaque regions corresponding to areas of the resist layer that are exposed and not exposed by activating radiation, respectively. The exposure wavelength is typically below 500 nm, such as UV-visible light from 200-500 nm. Preferably, the exposure is with 365 nm wavelength radiation (i-line) from a mercury lamp.
[0056] After the exposure of the photoresist composition layer, a post-exposure bake (PEB) is typically performed to decompose the acid labile group by the acid generated from the PAG during the exposure process. PEB can be performed, for example, on a hot plate or in an oven. This forms a latent image defined by the boundary between the polarity-switched and non-switched regions (corresponding to the exposed and unexposed regions, respectively).
[0057] The photoresist composition layer is then contacted with an alkaline developer to remove the exposed portions of the layer, leaving the unexposed regions forming a resist pattern. The developer is typically an aqueous alkaline developer, such as a quaternary ammonium hydroxide solution, for example a tetraalkylammonium hydroxide solution, such as 0.26 normality (N) (2.38 wt %) tetramethylammonium hydroxide (TMAH).
[0058] A further aspect is a process for depositing metal on the metal layer 102. Figure ID is an exemplary depiction of the deposition (by plating) of metal 112 on the metal layer 102. The process includes immersing the metal layer in a metal plating solution and electrolytically depositing metal onto the metal layer in the exposed portions of the photoresist composition layer. The metal layer 112 is typically formed on the substrate or on the exposed portions of the first metal layer 102.
[0059] The substrate with the patterned photoresist layer 106 can be immersed in a metal plating solution to plate metal onto the exposed first metal layer in the areas where the photoresist composition layer has been developed away. The developed areas of the photoresist composition layer act as a template for metal plating. The metal can be plated, for example, by electroplating. Various types of metal plating solutions known in the art can be used. Two or more different layers of metal can also be formed, and the layers can be of the same or different metals. Preferred plating metals include, but are not limited to, copper, nickel, tin, silver, gold, and mixtures and alloys thereof. Metal plating solutions suitable for use in forming such metals are known in the art and are supplied by DuPont Electronics & Industrial. The thickness of the plated metal layer is typically 1 to 100 micrometers, preferably 5 to 50 micrometers. The plated metal layer thickness can be less than or greater than the thickness of the photoresist layer.
[0060] After metal plating, the remaining photoresist layer can be removed (stripped) from the substrate, leaving behind plated metal structure 112. Figure IE shows the plated metal structure 112 remaining after removal of the remaining photoresist layer. Suitable photoresist strippers are available, for example, from DuPont Electronics & Industrial.
[0061] The exposed first metal layer between the plated metal structures can be optionally removed, for example, by an etch-back process, to electrically insulate each of the plated metal structures. The resulting metal structures can have line shapes that can be useful, for example, in a redistribution layer to provide electrical connection between two components. Advantageously, metal lines with small widths and straight (vertical) sidewalls can be formed by the compositions and methods disclosed herein. Such structures find use, for example, in electrical connections in small, lightweight, and thin devices. The width of the line can be, for example, 0.8 to 100 micrometers, preferably 1 to 50 micrometers. The height of the line will depend, for example, on the thickness of the photoresist composition resin, but pillar heights of 2 micrometers or more can be formed.
[0062] The present invention is advantageous in that the photoresist compositions can be used to obtain lines with a larger cross-sectional area at the base of the pillar compared to the cross-sectional area at the top of the pillar. The use of the disclosed photoresist compositions prevents the formation of undercuts at the bottom of the metal lines, thereby preventing the collapse of the lines during further processing of the semiconductor.
[0063] The invention will now be illustrated by the following non-limiting examples. EXAMPLES
[0064] Example 1 This example was carried out to demonstrate the use of a photoresist composition comprising a first basic quencher and a second basic quencher, where the second basic quencher comprises an azole that reduces tailing. It was also carried out to determine the specific substituents and the location of the substituents that can significantly affect the tailing profile. The example demonstrates which specific azole analogs can be used to minimize tailing in a photoresist layer.
[0065] The photoresist composition (used in this example) comprises a polymer comprising repeat units having an acid labile group, repeat units comprising hydroxystyrene, and repeat units comprising styrene, as seen in formula (7) below: The polymer comprises a copolymer of poly(4-hydroxystyrene) in the amount of 70 mol %, polystyrene in the amount of 10 mol %, and poly(tertbutyl acrylate) in the amount of 20 mol %, based on all polymerized units present in the polymer. [ka]
[0066] The polymer of formula (7) has a weight average molecular weight of 21,700 grams / mole, determined using a styrene standard.
[0067] As photoacid generators (PAGs), NHNI-TF (methanesulfonic acid, 1,1,1-trifluoro-, 1,3-dioxo-1H-benz[de]isoquinolin-2(3H)-yl ester) and NHNI-PFBS (1,3-dioxo-1H-benzo[de]isoquinolin-2(3H)-yl 1,1,2,2,3,3,4,4,4-nonafluorobutane-1-sulfonate) (Toyo Gosei Co., Ltd.) shown below were used. The first basic deactivator was Troeger's base (2,8-dimethyl-6H,12H-5,11-methanodibenzo[b,f][1,5]diazocine) (FUJIFILM Wako Pure Chemical Industries, Ltd.). This was diluted into a 1 wt% PGMEA solution. This was then filtered through a 0.45 μm PTFE filter to remove insoluble impurities. [ka]
[0068] Plasticizer LUTONAL™ M40 (polyvinyl ethyl ether) (BASF Japan Ltd.) and surface leveling agent (SLA) POLYFOX™ PF-656 (OMNOVA Solutions Inc.) were provided. PGMEA (propylene glycol monoethyl acetate), PGME (1-methoxy-2-propanol), and gamma-butyrolactone were mixed together and used as a solvent for the photoresist composition. The components were placed in a polypropylene bottle and stirred overnight at a rotation speed of 10 rpm using a roller shaker (Roller Digital 10, IKA® Japan Ltd.). After confirming the dissolution of the components, filtration was performed using a PTFE membrane filter with a pore size of 10 μm.
[0069] The composition of each sample is given in each section of the respective table. The weights of the PAG, base quencher and other additives such as SLA, plasticizers, solvents and other components are given as parts by weight per 100 parts of polymer (pbw). Additionally, the amount of second base quencher added is also given as a molar ratio of the PAG.
[0070] A 150 nm thick titanium layer was deposited on a 150 mm silicon substrate. A 200 nm thick copper layer was then deposited on the titanium layer by sputtering. The surface of the copper layer was cleaned with a 10 wt % sulfuric acid (H2SO4) solution for 30 seconds to remove the surface oxide layer, followed by rinsing with deionized (DI) water. A pressurized nitrogen stream was then blown onto the substrate to remove moisture. The substrate was paddle coated with a 2.38 wt % TMAH solution for 60 seconds, followed by rinsing with deionized water. The substrate was then spun dry.
[0071] The photoresist composition was then spin-coated onto the copper layer using a Sokudo D-Spin 60A SK-W60A-AVP wafer track, with the spin speed adjusted to obtain a 50 micrometer (μm) thick photoresist layer after a 135° C. soft bake for 6 minutes.
[0072] The photoresist layer was then subjected to broadband UV exposure using a multi-tone exposure mask with square contact hole patterns of various dimensions in a proximity mask aligner MA-1200 manufactured by Dainihon Kaken Co., Ltd. A post-exposure bake (PEB) was performed at 90°C for 3 min.
[0073] The exposed photoresist layer was then puddle developed four times for 60 seconds each using a 2.38 wt% TMAH aqueous developer (MF® CD-26, DuPont Electronics & Industrial). After development, the substrate was rinsed with water and spun dry.
[0074] The width of the contact holes was measured from top-view images taken using an optical microscope (H300, Lasertec Corporation, using LIBRA software). Cross-sectional images of the contact holes were obtained using a scanning electron microscope to determine the amount of tailing that occurred. Images were taken at 50x magnification.
[0075] Example 2 The solubility of the compounds shown in Table 1 in Figure 2 was determined by human eye using 1 wt% PGMEA solution. pKa values were obtained from SciFinder n+.
[0076] Table 2 shows different formulations of photoresist compositions that were evaluated to determine which second basic quenching agent exhibited useful sensitivity. All samples in Table 2 used Troeger's base as the first basic quenching agent. From Table 2 below, it can be seen that Samples #1-3 used 2-mercapto 5-methoxybenzothiazole (MBT) as the second basic quenching agent, and Samples #4-6 used 2-mercaptobenzoxazole (MBO) as the second basic quenching agent. Samples #7-9 used benzotriazole as the quenching agent. The molar ratio of the second basic quenching agent to the PAG was varied from 0.09 to 0.21 to 0.33. Two PAGs, specifically NHNI-PFBS and NHNI-TF, were used in amounts of 0.41 and 0.29 parts by weight per 100 parts by weight of polymer. Samples #1-3 and #7-9 are comparative examples, while Samples #4-6 illustrate the present invention.
[0077] [Table 1]
[0078] The formulations in Table 2 were used in photoresist compositions to determine which second base quencher produced the highest sensitivity in the photoresist composition. The molar loading levels of the second base quencher in each photoresist composition were adjusted to be equal to each other when compared to the total molar loading of PAG in the photoresist composition. Sensitivity is defined as the exposure energy that gives the same pattern size (or hole width) for each photoresist composition. A smaller value (amount) of exposure energy (i.e., less exposure energy to produce the same pattern size) indicates a higher sensitivity of the photoresist composition compared to photoresist compositions that use a higher amount of exposure energy. Photoresist compositions with higher sensitivity (using less exposure energy) are better in terms of energy consumption and productivity. Table 3 in Figure 3 shows the sensitivity of three different photoresist compositions (containing 2-mercapto 5-methoxybenzothiazole (MBT), benzotriazole (BTA), or 2-mercaptobenzoxazole (MBO)) when used to form 25 micrometer holes. 2-Mercaptobenzoxazole (MBO) exhibits the lowest energy exposure (and therefore the best sensitivity) of the three compounds when used in photoresist compositions.
[0079] FIG. 4 shows the relationship between the molar ratio (of second base quencher to PAG) present in each composition and the exposure energy (E op FIG. 4 is a graph showing the exposure energy (E) shown in FIG. 3 for forming a 25 micrometer hole. op ) is a graphical representation of the photosensitivity of the photoresist composition. The plot thus reflects the sensitivity of the photoresist composition. 2-mercaptobenzoxazole (MBO) exhibits the lowest energy exposure (and therefore the best sensitivity) of the three second base quencher compounds when used in the photoresist composition.
[0080] Figure 5 is a plot of the weight loss of each of the second basic quenching agents over the temperature range from 50°C to their respective thermal decomposition temperatures, as determined using thermogravimetric analysis, and shows that 2-mercaptobenzoxazole (MBO) exhibits superior thermal stability to BTA or MBT.
[0081] Example 3 This example was conducted to determine the effect of varying the ratio of the first base quencher to the second base quencher in a photoresist composition.
[0082] To evaluate the effect of patterning the profile, the amount of the first basic deactivator (Tröger's base) was increased relative to the second basic deactivator (2-mercaptobenzoxazole) (see Table 4). The loading amount of the second basic deactivator (2-mercaptobenzoxazole), which shows copper passivation effect, was fixed at 0.053 pbw per 100 parts by weight of polymer. The first basic deactivator was varied from 0.038 pbw to 0.050 pbw to 0.063 pbw. Cross-sectional pattern profiles of 25, 20 and 15 μm contact hole patterns were formed with exposure energies that achieved a nominal size (Eop) of 25 μm.
[0083] [Table 2]
[0084] As can be seen in Table 5 shown in FIG. 6, all samples exhibited narrow skirting regardless of sidewall angle. [Explanation of symbols]
[0085] 100 Substrates 102 Metal layer 106 Photoresist layer 108 Activating radiation 110 Photomask 112 Plated metal structure
Claims
1. A first repeat unit of formula (3) and a second repeat unit of formula (4): 【Chemistry 1】 (In the formula, R 1 represents a hydrogen atom or a substituted or unsubstituted C 1 ~C 3 alkyl, and Z is a non-hydrogen substituent containing an acid labile moiety. A polymer comprising Formula (6): 【Chemistry 2】 (In the formula, R 2 is independently 1 ~C 3 Alkyl or C 1 ~C 3 alkoxy, and p is an integer from 0 to 4. and A photoacid generator; Solvent and 1. A photoresist composition comprising:
2. 2. The photoresist composition of claim 1, further comprising a basic quencher different from the compound of formula (6).
3. 3. The photoresist composition of claim 2, wherein the basic quencher is selected from N-diethyldodecanamide, 2,8-dimethyl-6H,12H-5,11-methanodibenzo[b,f][1,5]diazocine (Tröger's base), 1,1-dimethylethyl 4-hydroxypiperidine-1-carboxylate, N-allylcaprolactam, ethyl-3-(morpholino)propionate, 4-(p-tolyl)morpholine, or combinations thereof.
4. 4. The photoresist composition of claim 2, wherein the molar ratio of the basic quencher to the compound of formula (6) is from 0.01:1 to 0.5:
1.
5. The photoresist composition according to any one of claims 1 to 4, wherein the photoacid generator is selected from N-hydroxynaphthalimide trifluoromethanesulfonate, N-hydroxynaphthalimide perfluoro-1-butanesulfonate, N-hydroxynaphthalimide camphor-10-sulfonate, N-hydroxynaphthalimide 2-trifluoromethylphenylsulfonate, N-hydroxy-5-norbornene-2,3-dicarboximide perfluoro-1-butanesulfonate, N-(trifluoromethylsulfonyloxy)phthalimide and N-hydroxysuccinimide perfluorobutanesulfonate.
6. The photoresist composition of any one of claims 1 to 5, wherein the molar ratio of the compound of formula (6) to the photoacid generator is from 0.01:1 to 0.5:
1.
7. The photoresist composition according to any one of claims 1 to 6, wherein the compound of formula (6) is 2-mercaptobenzoxazole.
8. 1. A photoresist composition comprising: (a) a polymer; (b) one or more photoacid generators; (c) a base quencher; (d) a mercaptobenzoxazole compound; and (e) a solvent; The polymer comprises the following two repeat units: 【Chemistry 3】 (In the formula, R 1 represents a hydrogen atom or a substituted or unsubstituted C 1 ~C 3 alkyl, and Z is a non-hydrogen substituent providing an acid labile site. Including, The photoacid generator is selected from N-hydroxynaphthalimide trifluoromethanesulfonate, N-hydroxynaphthalimide perfluoro-1-butanesulfonate, N-hydroxynaphthalimide camphor-10-sulfonate, N-hydroxynaphthalimide 2-trifluoromethylphenylsulfonate, N-hydroxy-5-norbornene-2,3-dicarboximide perfluoro-1-butanesulfonate, N-(trifluoromethylsulfonyloxy)phthalimide, and N-hydroxysuccinimide perfluorobutanesulfonate; the basic quenching agent is selected from N-diethyldodecanamide, 2,8-dimethyl-6H,12H-5,11-methanodibenzo[b,f][1,5]diazocine (Tröger's base), 1,1-dimethylethyl 4-hydroxypiperidine-1-carboxylate, N-allylcaprolactam, ethyl-3-(morpholino)propionate, 4-(p-tolyl)morpholine, or a combination thereof; The mercaptobenzoxazole compound is represented by the formula (6): 【Chemistry 4】 (In the formula, R 2 is independently 1 ~C 3 Alkyl or C 1 ~C 3 alkoxy, and p is an integer from 0 to 4. The A photoresist composition, wherein the solids content of the photoresist composition is 10 to 60% by weight.
9. 9. The photoresist composition of claim 8, wherein the second basic quencher is 2-mercaptobenzoxazole.
10. (i) providing a substrate comprising a metal layer on a surface of the substrate; (ii) forming a photoresist layer on the metal layer, the photoresist layer being formed from a photoresist composition according to any one of claims 1 to 9; (iii) patternwise exposing the photoresist layer to activating radiation; (iv) contacting the photoresist layer with an alkaline developer to remove exposed portions of the photoresist layer; (v) immersing the substrate in a metal plating solution and depositing metal on the metal layer in the exposed portions of the photoresist layer; A process including.
Citation Information
Patent Citations
Polymers and photoresist compositions for short wavelength imaging
EP0930542A1
Photoresist compositions comprising itaconic anhydride polymers
EP1008913A1
Photoresist compositions and methods of forming photolithographic patterns
US20120064456A1
Photoresist composition
US5492793A
Energy-sensitive resist material and a process for device fabrication using an energy-sensitive resist material
US5843624A